2013
DOI: 10.1371/journal.pone.0068966
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Expression of Mig6 and EGFR Is Associated with Resistance to EGFR Kinase Inhibitors

Abstract: The sensitivity of only a few tumors to anti-epidermal growth factor receptor EGFR tyrosine kinase inhibitors (TKIs) can be explained by the presence of EGFR tyrosine kinase (TK) domain mutations. In addition, such mutations were rarely found in tumor types other than lung, such as pancreatic and head and neck cancer. In this study we sought to elucidate mechanisms of resistance to EGFR-targeted therapies in tumors that do not harbor TK sensitizing mutations in order to identify markers capable of guiding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 34 publications
3
42
1
1
Order By: Relevance
“…We evaluated pairs of cancer cell lines with wild type EGFR that were either sensitive or resistant to the EGFR TKI, erlotinib; lung carcinoma (H358/H1703 and Calu3/Calu6) and H&N cancer (SCC-S/SCC-R and JHU011/JHU028). Erlotinib-resistant (SCC-R) and erlotinib-sensitive (SCC-S) isogenic cell lines were generated by chronic exposure of human H&N squamous cell carcinoma UM-SCC1 cells to either erlotinib or DMSO (vehicle control) (24). The other three pairs of cell lines (JHU011/JHU028, H358/H1703 and Calu3/Calu6) are intrinsically erlotinib-sensitive or erlotinib-resistant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We evaluated pairs of cancer cell lines with wild type EGFR that were either sensitive or resistant to the EGFR TKI, erlotinib; lung carcinoma (H358/H1703 and Calu3/Calu6) and H&N cancer (SCC-S/SCC-R and JHU011/JHU028). Erlotinib-resistant (SCC-R) and erlotinib-sensitive (SCC-S) isogenic cell lines were generated by chronic exposure of human H&N squamous cell carcinoma UM-SCC1 cells to either erlotinib or DMSO (vehicle control) (24). The other three pairs of cell lines (JHU011/JHU028, H358/H1703 and Calu3/Calu6) are intrinsically erlotinib-sensitive or erlotinib-resistant.…”
Section: Resultsmentioning
confidence: 99%
“…Drug resistant cell-lines were generated via a process of slowly escalating exposure to erlotinib, as reported previously (24). SCC-S is used to designate the parental UM-SCC1 cells exposed to DMSO, and SCC-R refers to the erlotinib resistant clone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study evaluated the relative expression level of MIG6 and EGFR in a small cohort of lung cancer patients treated prospectively with gefitinib. This study concluded that a lower MIG6/EGFR ratio is associated with sensitivity to TKIs, whereas a higher MIG6/EGFR ratio is a predictor of TKI resistance (56). In another study, ratio of MIG6 and miR200c RNA levels correlated with EMT and resistance to erlotinib (57).…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] It is possible, of course, that the two footprints were separated in evolutionary time, with the 3 0 -tigger footprint resulting from a gene conversion involving the nascent SH3-MHC gene, e.g., via an ABL kinase exchange with a GTPaselike gene harboring the nascent NefL structures. [26][27][28] Finally, the inherent resistance of C. atys to SIV disease, [29][30][31] suggests that some biology linked to the Loc-105576907 orf might afford novel explanations, and quite possibly novel approaches to HIV-1 therapeutics. The T. syrichta Loc-103275158 orf is (as we have discussed) one such piece of biology.…”
Section: Gov) H (Helix) Hth (Helix-turn-helix) Hss (Helix-strand-smentioning
confidence: 99%